Peningkatan kemampuan berpikir kritis dalam pembelajaran IPAS melalui Project Based Learning(PjBL) pada siswa kelas 4C sekolah dasar - 'Azizah Nur Zahra; Chumdari Chumdari; Roy Ardiansyah (Didaktika Dwija Indria, 2026)
This study was motivated by the low critical thinking skills of elementary school students in learning Natural and Social Sciences (IPAS). The research aimed to improve students’ critical thinking skills through the implementation of the Project Based Learning (PjBL) model. This study employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, implementation, observation, and reflection. The subjects were 28 students of grade 4C at SD Negeri Kemasan 1 Surakarta during the second semester of the 2023/2024 academic year. Data were collected through written tests, observation, and interviews, and analyzed using both descriptive quantitative and qualitative approaches. The findings indicated a significant improvement in students’ critical thinking skills from the pre-action stage to cycle II. The average score increased from 56.8 (pre-action) to 66.4 (cycle I), and reached 83.2 (cycle II). The percentage of students achieving the mastery level also increased from 21% (pre-action), 28% (cycle I), to 89% (cycle II). These results demonstrate that the structured application of PjBL, even with simple projects, can effectively enhance elementary school students’ critical thinking skills.